SISTEM INFORMASI PENJUALAN SAYUR MAYUR BERBASIS WEBSITE MENGGUNAKAN METODE USER CENTERED DESIGN - Aprilia Tika Rahayu; Septi Andryana (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
Toko Sayur Mayur Om Hendrik runs a vegetable shopping transaction between seller and buyer directly. Uncle Hendrik's store often get many complaints because of sudden cost increase of vegetable. Therefore, we need a platform for promotion, an information system that can be used for sales transactions, and ordering via WhatsApp. The client and server sides of this system are constructed. The system's foundation is a website written in the PHP programming language and a MySQL database. The UCD (User Centered Design) method was utilized to create this website, and a UML (Unified Modeling Language) diagram was used to explain the system design study. The built-in vegetable sales information system includes automatic periodic report production, information on the availability of vegetable stock, and online vegetable message services linked to WhatsApp chat. This information system is intended to give a huge contribution for Toko Sayur Mayur Om Hendrik